Case Report: Prenatal Diagnosis of a Novel Variant c.251dupT (p.N87Kfs*6) in BCOR Resulting in Oculofaciocardiodental Syndrome Using Whole-Exome Sequencing - Zhuang, Jianlong; Chen, Chunnuan; Chen, Yu’e; Zeng, Shuhong; Jiang, Yuying; Wang, Yuanbai; Chen, Xinying; Xie, Yingjun; Wang, Gaoxiong (Frontiers in Genetics, 2022)
Background: Oculofaciocardiodental (OFCD) syndrome is an X-linked dominant syndrome caused by BCOR variants, which manifests only in females and presumed leading to male lethality. Herein, we aim to present a prenatal diagnosis for OFCD syndrome associated with a novel hemizygous variant in BCOR gene. Case presentation: A 29-year-old pregnant woman from Quanzhou Fujian Province, China, with fetal ultrasound anomalies, was enrolled in this study. A normal 46, XY karyotype with no abnormalities was observed in the fetus detected on microarray. Furthermore, a whole-exome sequencing (WES) detection result demonstrated that a novel hemizygous variant of c.251dupT (p.N87Kfs*6) in the BCOR gene was identified in the fetus, which was a frameshift mutation and classified as a likely pathogenic variant, and may lead to OFCD syndrome according to the clinical feature of the fetus. In this case, male lethality had not occurred by the end of the second trimester, then termination of the pregnancy was conducted at a gestational age of 26 weeks. Sanger sequencing of parental samples revealed that the variant was maternally transmitted, which was consistent with the OFCD syndrome phenotypic features observed in her. Conclusions: In the study, we first present the affected male with a novel variant in BCOR that leads to the OFCD syndrome. Additionally, our study broadened the spectrum of BCOR results in the OFCD syndrome and provided the valuable references for prenatal genetic consultation.